HUBUNGAN AGIHAN JENIS TUMBUHAN DENGAN TEKSTUR TANAH DI HUTAN MANGROVE TELUK BUO KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Kumalasari, Nesya; Eka Putri, Irma Leilani; Rizki, Rizki (Pendidikan Biologi, 2013)
ABSTRACT Soil is one of important factors directly affecting growth and development of mangrove forest. The relationship between mangrove and soil is complemented by the ability of different types of mangrove to grow in different substrates. Rhizopora apiculatais distributed in all textures of soil (loam, sandy loam, clay loam, sandy clay loam, clay and loam sandy). Sonneratia caseolarisis distributed in loam, sandy loam, clay loam, sandy clay loam and clay. Aegiceras corniculatumis distributed in loam, sandy loam, sandy clay loam and loam sandy. Dolichandrone spathacea is distributed in loam, sandy loam, clay loam, and sandy clay loam. Bruguiera gymnhorrizaand Hibiscus tiliaceus are distributed in loam,sandy loam, and sandy clay loamwhile Acanthus ilicifolius is distributed in loam and sandy clay loam. This study aims to comprehend the relation between the distribution of the plant with the texture of soil in the mangrove forest of  teluk  buo in the subdistrict of bungus teluk kabung in the city of padang. This deskriptive work was performed form June to July, 2013. Samples were colected from a 10 m by 10 m study plot placed along transection line from the star of shoreline until the border between mangrove and land forest. At the study location  transections were created with the lenght of 160 m (transection 1) and 180 m (transection 2). With the distance between recorded for each plot, knows plants were recorded on the spot while the unknows were collected at mangrove forest of the teluk buo and soil textures were determined at the laboratories. The study found that there are six types of soil textures in the area consisted of loam,sandy loam, clay loam, sandy clay loam, clay and loam sandy. Distributed plants were identified as Rhizophora apiculata, Sonneratia caseolaris, Aegiceras corniculatum. Bruguiera gymnhorriza, Dolichandone spathacea, Acanthus ilicifolius, and Hibiscus tiliaceus.